Flood Disaster and Its Impact on Livelihood: A Case of Kandra River Basin of Kailali District - Pangali Sharma, Bishnu Prasad (NUTA Journal, 2018)
This paper tried to highlights impact of flood disaster on local livelihood in Kandra river basin, Kailali District. The study also examined coping strategies of the members of flood affected village community. In so doing, required data and information were collected and generated through household survey, semi-structured interviews as well as focus group discussions, key informant interview and observations. There are almost 50 settlements in the river basin; whereas 15 settlements are along with Kandra River. Three settlements: Kanhaiyapur, Thengarpuruwa and Lalbojhi; are most frequently affected from flood disaster that were selected for the study purpose. Thirty households from each settlement have been selected for household questionnaire. Satellite images and aerial photos are used to analyze terrain, channel course. The study finds that all communities living in the low-lying area and along the riverbank are affected from flood disaster. However, not all people are vulnerable equally. To cope with this problem, local people have designed and practicing various adaptation techniques. The adaptation strategy differs based on their socio-economic condition, such as education, income, occupations and living conditions. Establishment of early warning system and capacity building of flood victims will help to cope with disasters.